Circular Path Following for the Spherical Pendulum on a Cart. Issue 1 (July 2017) - Greco, Luca; Mason, Paolo; Maggiore, Manfredi
Abstract: This paper investigates the problem of making the cart of a spherical pendulum follow a circular path with constant speed, while guaranteeing that the pendulum does not fall over. A solution methodology is presented which is hierarchical in nature. First, one of the two control inputs is used to stabilize the angle of the pendulum from the vertical axis at a constant value. The remaining control input is used to make the cart converge to the circular path with a desired speed.